Fred Ferguson and Graffiti: Fresh Paint - Thomas, Shavincia J. (International Journal of Bahamian Studies, 2013)
Living up to its name, the CD Fresh Paint certainly introduces a revamp to Bahamian favorites. Performed by Fred Ferguson and Graffiti, this exciting CD quickly captures the attention of listeners.